2021
DOI: 10.22438/jeb/42/4/mrn-1558
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of rock phosphate with single super phosphate on yield and phosphorus use efficiency under maize-groundnut cropping sequence in Alfisols of Odisha

Abstract: Aim: The present study was conducted to investigate the effect of combined application of rock phosphate with water soluble phosphorus fertilizers on its efficiency in relation to soil and crop production. Methodology: Rock phosphate and single super phosphate were used as supplemental source of phosphorus and applied in variable combinations at graded doses, with maize and groundnut as test crop. Lime was applied in combination with 100% SSP to analyse its effect. The composite surface (0-15 cm) soil samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Rock phosphate has a greater potential to improve soil health than triple super phosphate. Rock phosphate releases P slowly to the soil for plant uptake unlike triple super phosphate that appeared fixed in the soil (Sarkar et al, 2018;Sarangi et al, 2020;Mohanty et al, 2021).…”
Section: Response Of Urea P-sources and Biochar To Potato Growth And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rock phosphate has a greater potential to improve soil health than triple super phosphate. Rock phosphate releases P slowly to the soil for plant uptake unlike triple super phosphate that appeared fixed in the soil (Sarkar et al, 2018;Sarangi et al, 2020;Mohanty et al, 2021).…”
Section: Response Of Urea P-sources and Biochar To Potato Growth And ...mentioning
confidence: 99%
“…In the second experiment, it was observed that application of rock phosphate and triple super phosphate significantly increased cation exchange capacity and organic carbon in the soil. This means that either of the nutrients could be applied to support the residual of level of cation exchange capacity and organic carbon (Mohanty et al, 2021).…”
Section: The Residual Level Of Nutrients In the Soil After Potato Har...mentioning
confidence: 99%